Living with insecurity in a Brazilian favela : urban violence and daily life - Penglase, Ben (Rutgers University Press, 2014)
The residents of Caxambu, a squatter neighborhood in Rio de Janeiro, live in a state of insecurity as they face urban violence. Living with Insecurity in a Brazilian Favela examines how inequality, racism, drug trafficking, police brutality, and gang activities affect the daily lives of the people of Caxambu. Some Brazilians see these communities, known as favelas, as centers of drug trafficking that exist beyond the control of the state and threaten the rest of the city. For other Brazilians, favelas are symbols of economic inequality and racial exclusion. Ben Penglase's ethnography goes bey.